It Must Be My Favourite Brand: Using Retroactive Brand Replacements in Doctored Photographs to Influence Brand Preferences. Issue 6 (21st September 2016) - Hellenthal, Maria V.; Howe, Mark L.; Knott, Lauren M.
Summary: We examined whether memories for personally chosen brands could be altered by retroactive exposure to less‐liked competitor brands embedded in manipulated photographs. In addition, we investigated whether memory errors would lead to preference change for falsely remembered brands. Fifty participants were asked to compile their personal 'brand lifestyle basket', which was then captured in a photo showing the basket and participant. After 1 week, participants were exposed to the photograph in which some of the originally chosen brands were replaced by different brands of the same category. Results of a memory test revealed a robust misinformation effect. The analysis of premanipulation and postmanipulation preference ratings indicated a positive shift in attitude and behaviour towards falsely accepted misinformation brands. Our findings contribute to what we know about the behavioural consequences of false memories and extend the generalizability of false memory effects to what might be considered a futuristic advertising measure. Copyright © 2016 John Wiley & Sons, Ltd.